Impaired social cognition in anorexia nervosa patients - Hamatani S (Dove Medical Press, 2016)
Sayo Hamatani,1 Masahito Tomotake,2 Tomoya Takeda,1 Naomi Kameoka,3 Masashi Kawabata,3 Hiroko Kubo,3 Yukio Tada,3 Yukiko Tomioka,4 Shinya Watanabe,4 Tetsuro Ohmori4 1Graduate School of Medical Sciences, Tokushima University, 2Department of Mental Health, Institute of Biomedical Sciences, Tokushima University Graduate School, 3Department of Psychiatry, Tokushima University Hospital, 4Department of Psychiatry, Institute of Biomedical Sciences, Tokushima University Graduate School, Tokushima, Japan Background: The purpose of this study was to investigate the characteristics of social cognition in patients with anorexia nervosa (AN).Methods: Eighteen female patients with AN (mean age =35.4±8.6 years) and 18 female healthy controls (HC) (mean age =32.8±9.4 years) participated in the study. Their social cognition was assessed with the Social Cognition Screening Questionnaire (SCSQ).Results: The results showed that total score of the SCSQ and scores of theory of mind and metacognition were significantly lower in AN group than those in HC group. Moreover, significant differences in theory of mind, metacognition, and total score of the SCSQ remained when the effects of depression, anxiety, and starvation were eliminated statistically.Conclusion: These results suggest that patients with AN may have difficulty inferring other people’s intention and also monitoring and evaluating their own cognitive activities. Therefore, these features may explain some aspects of the pathology of AN. Keywords: anorexia nervosa, social cognition, theory of mind, metacognition